Persepsi Siswa Terhadap Penerapan Model Project Based Learning pada Mata Pelajaran Akuntansi Dasar - Rahmawati, Arlean; Pratiwi, Nova; Januardi, Januardi (Jurnal Pendidikan Ekonomi dan Akuntansi, 2024)
In the era of rapid globalization and digitalization, critical thinking, creativity, and collaboration have become very important in today's education.At SMK Negeri 3 Palembang, one of the teaching models currently used by teachers is the project-based learning model. The project-based learning (PjBL) model uses problems to gather and integrate new knowledge from their experiences in real activities. The purpose of this research is to determine students' perceptions of the implementation of the project-based learning model in the basic accounting subject at SMK Negeri 3 Palembang. On 3 aspects of indicators, namely cognitive, affective, and conative. This research method uses quantitative descriptive research with a Likert scale, where a questionnaire is used with alternative answers for each indicator, namely Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). (STS). The score for  SS is 4, S is 3, TS is 2, and STS is 1.The average research results show that students' perceptions of the implementation of the PjBL model in basic accounting subjects are very good. The conclusion of this research is that the application of this model is effective in enhancing students' learning motivation, activity, and understanding of basic accounting material. Therefore, it is recommended that this model be applied more widely and integrated with other learning models to achieve optimal results.Keywords: Perception, Project Based Learning, Basic Accounting Learning